Contribution of trunk muscularity on sprint run - Kubo, T.; Hoshikawa, Y.; Muramatsu, M.; Iida, T.; Komori, S.; Shibukawa, K.; Kanehisa, H. (International Journal of Sports Medicine, 2011)
This study aimed to investigate how the trunk muscularity is related to sprint running performance. In 23 youth soccer players, the cross-sectional images at the mid level of each of L1-L2, L2-L3, L3-L4, L4-L5, and L5-S1 were obtained using magnetic resonance imaging to determine the cross-sectional areas (CSAs) of rectus abdominis, oblique, psoas major, quadratus lumborum and erector spinae muscles. The times taken to sprint over 20 m were measured, and the mean velocity of running was calculated for each of the 2 distances (V10 m and V20 m) and for the distance from 10 m to 20 m (V10-20 m). The CSA values of the 5 slice levels for all muscles except for the quadratus lumborum and those of the 3 slice levels (L1-L2, L2-L3 and L3-L4) for the quadratus lumborum were averaged and expressed relative to the two-third power of body mass (CSA/BM2/3). The CSA/BM2/3 values of the erector spinae and quadratus lumborum were selected as significant contributors to predict V10 m (R2=0.450), V20 m (R2=0.504) and V10-20 m (R2=0.420). The current results indicate that the muscularity of the erector spinae and quadratus lumborum contributes to achieving a high performance in sprint running over distances of less than 20 m.